Counseling Ethics: The Case of Sexuality Information - Daniel Del Rio Forero; Claudia Pineda Marín; Diego Andrés Alfonso Murcia; María Teresa Muñoz Sastre; Etienne Mullet (Journal of Family and Reproductive Health)
Objective: The study aimed to identify Colombian adults' positions in cases in which a counsellor can and should not do so in a situation where parents who are uncomfortable with all issues related to sexuality ask their daughter's school counsellor to help answer her questions about these topics. Materials and methods: A convenience sample of 180 adults, including 19 school counsellors, was presented with a set of 24 vignettes created by orthogonally crossing three factors: (a) the context of the request (e.g., parents ask the educator to limit sexual information to purely biological aspects), (b) whether the adolescent requests additional information, and (c) the type of information provided by the educator (e.g., comprehensive information, including abortion). Results: A cluster analysis of participants' appropriateness judgments regarding counsellor’s behavior revealed four qualitatively different positions: Depends on adolescent’s request (5%), Completeness of information (26%), Biological information is insufficient (31%), and at educator's discretion (16%). In addition, 18% (most religious) expressed no discernible position. Conclusion: The majority of participants (57%) thus expressed the view that the most appropriate behavior on the part of the counselor was to provide the most comprehensive information possible, and certainly not to focus solely on the biological aspects of sex education during counseling. This view was largely independent of contextual elements such as the limits to communication set by the parents or even the limits to communication set by the adolescent.